2017
DOI: 10.1111/ejh.12996
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic microangiopathy with concomitant GI aGVHD after allogeneic hematopoietic stem cell transplantation: Risk factors and outcome

Abstract: Thrombotic microangiopathy with concomitant aGVHD is a significant complication after allo-HSCT, with a worse outcome, including significantly lower OS and higher NRM. There are specific risk factors associated with occurrence and mortality of this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
(144 reference statements)
1
6
0
Order By: Relevance
“…In our series, more than half of the patients who were diagnosed with TA-TMA with concomitant aGVHD died. This is also similar to previous reports from adults where Zhang et al 38 reported poor survival of 52% (n 5 50) among patients who developed TA-TMA vs 77% in patients who had only aGVHD (n 5 83) and 86.6% among patients who neither developed aGVHD nor TA-TMA and aGVHD (n 5 67) with higher nonrelapse mortality but low risk of relapse. Another group reported a drop in 90-day survival among patients with TA-TMA from 96% in patients with no documented driving factor to 50% in patients with concomitant GVHD.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our series, more than half of the patients who were diagnosed with TA-TMA with concomitant aGVHD died. This is also similar to previous reports from adults where Zhang et al 38 reported poor survival of 52% (n 5 50) among patients who developed TA-TMA vs 77% in patients who had only aGVHD (n 5 83) and 86.6% among patients who neither developed aGVHD nor TA-TMA and aGVHD (n 5 67) with higher nonrelapse mortality but low risk of relapse. Another group reported a drop in 90-day survival among patients with TA-TMA from 96% in patients with no documented driving factor to 50% in patients with concomitant GVHD.…”
Section: Discussionsupporting
confidence: 90%
“…Among the patient-derived risk factors, sex, and underlying disease did not influence the risk for TA-TMA, similar to data reported from previous studies. 16,35,38 On the contrary, others reported increased risk of TA-TMA among females more than males, whereas underlying disease had no impact. 21,39 In our cohort of patients, active comorbidity stood as a significant factor associated with TA-TMA.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The gastrointestinal tract is frequently involved in a variety of posttransplant complications, with GVHD being one of the most common after allo-HSCT, and gastrointestinal tract involvement is seen in 74% of patients with aGVHD [45] and 30% of patients with cGVHD [46]. More than half of all patients with severe gastrointestinal GVHD are reported to experience GIB [47], and other complications, such as conditioning toxicity, infection and TMA, often affect the gut [48,49]. Thus, the causes resulting in the occurrence of GIB after HSCT vary, and the time of GIB onset is not always fixed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also reported adverse outcomes in TA-TMA patients with concomitant diffuse alveolar hemorrhage 11 and acute GVHD. 24 Considering the low response rate of current treatment strategies, 3,6 severe cases that require immediate intensification of support need to be identified at an earlier stage, ideally as soon as the diagnosis of TMA. However, most of the clinical risk factors were not readily applicable at the initial presentation of disease.…”
Section: Introductionmentioning
confidence: 99%